Truncation error bounds for branched continued fraction whose partial denominators are equal to unity - R. I. Dmytryshyn; T. M. Antonova (Математичні Студії, 2020)
The paper deals with the problem of obtaining error bounds for branched continued fraction of the form $\sum_{i_1=1}^N\frac{a_{i(1)}}{1}{\atop+}\sum_{i_2=1}^{i_1}\frac{a_{i(2)}}{1}{\atop+}\sum_{i_3=1}^{i_2}\frac{a_{i(3)}}{1}{\atop+}…$. By means of fundamental inequalities method the truncation error bounds are obtained for the above mentioned branched continued fraction providing its elements belong to some rectangular sets of a complex plane. Applications are considered for several classes of branched continued fraction expansions including the multidimensional S-, A-, J-fractions with independent variables.